2021
DOI: 10.3389/fneur.2021.642664
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Analysis of Autoantibody-Associated CNS Demyelinating Disorders in Children in Southwest China

Abstract: Objective: To analyze the positive and recurrence rates of different autoantibody-associated demyelination disorders in children in Southwest China, and describe the clinical, radiological, and prognostic features of the myelin oligodendrocyte glycoprotein antibody (MOG-ab) and aquaporin-4 antibody (AQP4-ab) associated disease. This study also summarizes steroid maintenance therapy approaches for MOG-ab-positive children.Methods: A total of 160 children presenting with acquired demyelinating syndromes (ADS) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 38 publications
5
12
0
Order By: Relevance
“…We observed that the children with seropositive AQP4 antibody tended to be older than those with seropositive MOG antibody or seronegative AQP4-/MOG antibody, and a higher female:male ratio in AQP4 antibodypositive pediatric patients was not found in the children with positive MOG antibody or negative AQP4-/MOG antibody. A similar difference in the age and female:male ratio was observed in previous studies as well (6,28,29). We also found a difference in the spatial distribution of onset lesions in the children with different antibody types.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that the children with seropositive AQP4 antibody tended to be older than those with seropositive MOG antibody or seronegative AQP4-/MOG antibody, and a higher female:male ratio in AQP4 antibodypositive pediatric patients was not found in the children with positive MOG antibody or negative AQP4-/MOG antibody. A similar difference in the age and female:male ratio was observed in previous studies as well (6,28,29). We also found a difference in the spatial distribution of onset lesions in the children with different antibody types.…”
Section: Discussionsupporting
confidence: 91%
“…This general distribution of MOGAD phenotypes was also observed when assessing all identified studies (Table 1). Overall, 39 identified articles (including the six aforementioned incident cohort studies) reported the phenotype at initial presentation for 1,686 pediatric MOGAD patients 4–6,8,11–45 . Most of these studies were limited by the potential for selection bias in patient identification (e.g., patients with stored serum available for retrospective MOG‐Ab testing, relapsing disease course, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately two-thirds of the identified studies not included in Table 2 (i.e., not inception cohorts) reported the proportion of pediatric MOGAD patients with a relapsing course to be greater than 30%; however, this is likely a result of selection bias. For example, in one study the proportion of pediatric and adult MOGAD patients with a relapsing course was 50% among the entire identified study cohort (i.e., a convenience sample) but only 25% when restricted to patients with an incident diagnosis who were identified prospectively (42). With regards to relapses, it is important to note that number and frequency of relapses reported is highly dependent upon the duration of the follow-up and the effectiveness of any chronic treatments received, and these factors varied substantially across studies making definitive interpretation difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and radiological heterogeneity has age‐related differences in MOGAD. Younger children are more likely to have severe brain pathology and imaging involvement than older children (Fernandez‐Carbonell et al, 2016; Hacohen, Wong, et al, 2018; Li et al, 2021). In our study, the age at disease onset was under 6 years old, consistent with previous reports that typically children younger than 7 years are more prone to have leukodystrophy‐like brain lesions (Hacohen, Rossor, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%